2015
DOI: 10.1038/srep12528
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Coexistence of Bulk Superconductivity and Itinerant Antiferromagnetism in the Heavy Fermion System CeCo(In1−xCdx)5

Abstract: In the generic phase diagram of heavy fermion systems, tuning an external parameter such as hydrostatic or chemical pressure modifies the superconducting transition temperature. The superconducting phase forms a dome in the temperature—tuning parameter phase diagram, which is associated with a maximum of the superconducting pairing interaction. Proximity to antiferromagnetism suggests a relation between the disappearance of antiferromagnetic order and superconductivity. We combine muon spin rotation, neutron s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 58 publications
3
13
1
Order By: Relevance
“…Previous works have shown that Ce-M 4,5 -edge XANES spectra provide distinct signatures for the Ce 3+ and Ce 4+ oxidation states, although the ability to fully deconvolve mixtures of oxidation states is limited to about 5% for bulk materials 56,[65][66][67] . Spectra for the CeO 2 NPs closely resemble published O K-edge [68][69][70] and Ce M 5,4 -edge 56,[66][67][68][71][72][73] spectra for CeO 2 obtained using a variety of detection methods, which confirms that subsequent solution-phase studies were conducted on analytes that were pure and homogenous. Some very small shape distortions of the spectrum can be attributed to either the presence of the surface hydroxyl groups, or Ce(III) at the NP interface.…”
Section: X-ray Absorption Fine Structure (Xafs)supporting
confidence: 70%
“…Previous works have shown that Ce-M 4,5 -edge XANES spectra provide distinct signatures for the Ce 3+ and Ce 4+ oxidation states, although the ability to fully deconvolve mixtures of oxidation states is limited to about 5% for bulk materials 56,[65][66][67] . Spectra for the CeO 2 NPs closely resemble published O K-edge [68][69][70] and Ce M 5,4 -edge 56,[66][67][68][71][72][73] spectra for CeO 2 obtained using a variety of detection methods, which confirms that subsequent solution-phase studies were conducted on analytes that were pure and homogenous. Some very small shape distortions of the spectrum can be attributed to either the presence of the surface hydroxyl groups, or Ce(III) at the NP interface.…”
Section: X-ray Absorption Fine Structure (Xafs)supporting
confidence: 70%
“…The commensurate magnetic order with Q AF = (1/2, 1/2, 1/2) determined here for CeIr(In 0.9 Cd 0.1 ) 5 is also strikingly different from that in pure CeRhIn 5 , in which an incommensurate magnetic structure with Q AF = (1/2, 1/2, 0.297) was reported 24,[32][33][34] . On the other hand, the same commensurate magnetic ordering wave vector was observed in Cd-doped CeCoIn 5 [18][19][20] , in which superconductivity coexists with magnetic order over a wide range of Cd concentrations (Fig. 1(a)).…”
Section: Resultssupporting
confidence: 59%
“…To determine the Néel temperature, the data were fitted by a phenomenological function I/I 0 = 1 − (T /T N ) α , with α a free parameter. This function was successfully used to fit the temperature dependence of the magnetic Bragg peak intensity in other heavy fermion compounds, such as CePd 2 Si 2 25,26 , Sn-doped CeRhIn 5 12 , Cd-doped CeRhIn 5 18 , and CePt 2 In 7 27 . The best fit is obtained with α = 2.0 ± 0.5 and T N = 3.0 ± 0.1 K. The latter value is consistent with T N determined from previous specific heat 17 and resistivity 22 measurements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations